Lifelines of our society a global history of infrastructure - Laak, Dirk van 1961- (The MIT Press, 2023)
"A global history of modern infrastructures covering two centuries of historical dynamics from all over the world"--
Literaturverzeichnis Seite [259]-309. - Index
Keywords: Geschichte; Geschichte 1800-2000; Infrastruktur; Technischer Fortschritt; Moderne; Alltag; Infrastructure (Economics) / History